(Re)Presentation of “the” Past in Berlin-Mitte after German Reunification, and Its Implications for Cultural Production through Appropriation of Space - Mary Dellenbaugh ([sic])
This paper examines the appropriation of space for cultural production in Berlin’s central district Mitte in the years directly after German reunification (approximately 1990-1994) and suggests an explanatory model for the intensity of and motivations behind these changes. The research conducted for this paper used interviews, discourse analysis and historical research to identify three main impulses that guided spatial changes in Berlin’s central district Mitte directly after reunification: the divergent post-war development of the two Germanys, the political and structural aspects of reunification, and the moving of the German capital back to Berlin after 40 years in Bonn. The author posits that these changes represent not only “simple” physical and symbolic appropriation, but also a proxy for the reinterpretation of the German national narrative after 1990. In the conclusion, the author discusses the role of Vergangenheitsbewältigung (“coming to grips with the past”) and divided development as pivotal to the spatial developments in Berlin’s central district after reunification.